Architektur eines workflowbasierten Planungsinstruments für die technische Auftragsbearbeitung unter besonderer Berücksichtigung des Einsatzes der Telearbeit - Kress, Stephan

Integrierte Methodik zur Gestaltung von Leistungserstellungsprozessen mittels Workflowmanagement - Thielemann, Frank

Modelle zur Untersuchung des Schwingungsverhaltens von Statoren für piezoelektrische Ultraschall-Wanderwellen-Motoren - Krome, Jürgen

Modellierung als Kernfunktion einer systemorientierten Analyse und Bewertung der diskreten Produktion - Langemann, Timo

Integration von Methoden und Werkzeugen zur Entwicklung von mechatronischen Systemen - Kümmel, Martin

Proceedings of the 1st International Khepera Workshop: Experiments with the Mini-Robot Khepera

: Personalcontrolling und Recht - Fallbeispiele und deren juristische Lösung - - Krimphove, Dieter; Seitz, S. (Personalinformationssysteme & Personalcontrolling)

Kleben von Aluminium-Strangpreßprofilen – eine wärmearme Fügetechnik für eigenschaftsoptimierte Rahmenkonstruktionen - Koyro, M.; Meschut, Gerson (Tagungsband zu den 1. Duisburger Aluminiumtagen)

Frege, Gottlob, Zwei Schriften zur Arithmetik. Function und Begriff. Über die Zahlen des Herrn H. Schubert, hg. v. Wolfgang Kienzler, Olms: Hildesheim 1999 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete [Zbl. 916.01026])

Generating Random Star-Shaped Polygons - Sohler, Christian (Proceedings of the 11th Canadian Conference on Computational Geometry ('CCCG'99))
In this paper we deal with two problems on star-shaped polygons. First, we present a Las-Vegas algorithm that uniformly at random creates a star-shaped polygon whose vertices are given by a point set ( S ) of ( n ) points in the plane that does not admit degenerate star-shaped polygons. The expected running time of the algorithm is ( O(n^2log n) ) and it uses ( O(n) ) memory. We call a star-shaped polygon degenerate if its kernel has 0 area. Secondly, we show how to count all star-shaped polygons whose vertices are a subset of ( S ) in ( O(n^5log n) ) time and ( O(n) ) space. The algorithm can also be used for random uniform generation. We also present lower and upper bounds on the number of star-shaped polygons.

Design of the PRESTO Multimedia Storage Network (Extended Abstract) - Berenbrink, Petra; Riedel, Marco; Scheideler, Christian (International Workshop on Communication and Data Management in Large Networks (CDMLarge))

Kleiner Antrieb, große Wirkung - Zimmer, Detmar (Der Konstrukteur - Magazin für Konstruktion und Entwicklung (ASB))

Der Einfluss von Steuern auf Investitionsentscheidungen bei Unsicherheit - Sureth-Sloane, Caren

From Static to Dynamic Routing: Efficient Transformations of Store-and-Forward Protocols - Scheideler, Christian; Vöcking, Berthold (STOC)

Informatik '99: Informatik überwindet Grenzen. Tagungsband der 29. Jahrestagung der Gesellschaft für Informatik, Paderborn (Germany)

Patterns as a Means for Intelligent Software Engineering - Deugo, Dwight; Küster, Jochen; Oppacher, Franz; von Otte, Ingo (Proceedings of the conference on Artificial Intelligence (IC-AI 1999) Las Vegas, Nevada (USA))

Tile Transition Systems as Structured Coalgebras - Corradini, Andrea; Heckel, Reiko; Montanari, Ugo (Proceedings of the 12th International Symposium on Fundamentals of Computation Theory (FCT '99))

Application of the Structured Analysis and Design Technique (SADT) Methodology for the Medical Information Systems Development - Cherchago, Alexey (Proceedings of the All-Russia Students’, Young Scientists’ and Specialists’ Scientific and Technical Conference "New Information Technologies in Scientific Researches and in Education" (Ryazan, Russia))

Konzeption und objektorientierte Realisierung einer internet-basierten Datenbankanwendung - Engels, Gregor; Depke, Ralph; Borowski, Christoph (Kolloquium Software-Entwicklung - Methoden, Werkzeuge, Erfahrungen)
Today e-commerce applications use web browsers as an uniform user interface and they rely on databases as data sources. Different technologies exist for database access: common gateway interface (CGI), Java and its database interface java database connectivity (JDBC), proprietary approaches of database vendors, etc. We present criteria for the selection of an appropriate solution and we successivly apply them in our application development process. Throughout the development process of internet based database applications object oriented techniques can be used. The unified modeling language (UML) is used for requirement analysis and design of the application and the implementation proceeds with the programming language Java. The transition from the object oriented modeling language UML to the object oriented programming language Java succeeds smoothly. We report on our experience with the modeling tool Rational Rose 98 of Rational, Inc. We use Java and JDBC to implement a seminar reservation system that can be regarded as a small e-commerce application.

UML Collaboration Diagrams and Their Transformation to Java - Engels, Gregor; Hücking, Roland; Sauer, Stefan; Wagner, Annika (Proceddings of The Unified Modeling Language: Beyond the Standard, Second International Conference (UML 99), Fort Collins, Colorado, USA)

A Bi-Categorical Axiomatisation of Concurrent Graph Rewriting - Gadducci, Fabio; Heckel, Reiko; Llabrés, Mercé (Proceedings of the 8th Conference on Category Theory and Computer Science (CTCS 1999), Edinburgh (UK))
In this paper the concurrent semantics of double-pushout (DPO) graph rewriting, which is classically defined in terms of shift-equivalence classes of graph derivations, is axiomatised via the construction of a free monoidal bi-category. In contrast to a previous attempt based on 2-categories, the use of bi-categories allows to define rewriting on concrete graphs. Thus, the problem of composition of isomorphism classes of rewriting sequences is avoided. Moreover, as a first step towards the recovery of the full expressive power of the formalism via a purely algebraic description, the concept of disconnected rules is introduced, i.e., rules whose interface graphs are made of disconnected nodes and edges only. It is proved that, under reasonable assumptions, rewriting via disconnected rules enjoys similar concurrency properties like in the classical approach.

Modeling Agent-Based Systems with Graph Transformation and UML - Heckel, Reiko (Proceedings of the Dagstuhl-Seminar 99451 on Rigorous Analysis and Design for Software Intensive Systems)

Extending UML for Modeling of Multimedia Applications - Sauer, Stefan; Engels, Gregor (Proceedings of the IEEE Symposium on Visual Languages (VL 1999), Tokyo (Japan))
An analysis of how visual modeling of structure and dynamic behavior of a multimedia application differs from modeling conventional software yields that aspects of the graphical user interface and time-dynamic behavior ought to be integral parts of a coherent multimedia application model. In this sense, we extend the model-view-controller paradigm towards multimedia.As a result, we present OMMMA-L, a visual Language for the Object-Oriented Modeling of MultiMedia Applications that is based on the Unified Modeling Language (UML). The structural and behavioral diagram types of UML have been analyzed and are adapted and extended according to multimedia application characteristics.A presentation diagram is introduced and integrated to adequately describe the visual presentation. In addition to explaining the different diagram types, we also give pragmatic guidelines on how to deploy and combine the various diagrams.

Combined Photovoltaic and Solar Thermal Systems for Facade Integration and Building Insulation - Salhi, M. J.; Krauter, Stefan; Lemoine, R.; Triebel, C.; Schroer, S.; Araújo, R. G. (Proceedings of the ISES Solar World Congress, Jerusalem (Israel), .4.–9. Juli 1999, II-88.)

Set-up of a Laboratory for Research and Education in Solar Energy in Rio de Janeiro - Krauter, Stefan; Stephan, R.; Bastos, L. (Proceedings of the ISES Solar World Congress, Jerusalem (Israel), 4.–9. Juli 1999, S. II-288)

Cooling and Less Reflections at Photovoltaic Modules by a Frontside Water Film. - Krauter, Stefan; Schmid, U. (Proceedings of the ISES Solar World Congress, Jerusalem (Israel), 4.–9. Juli 1999,)

The Use of Solar Energy: Considerations for Calculations of Greenhouse Gas Reduction by Photovoltaics - Krauter, Stefan (Proceedings of the ISES Solar World Congress, Jerusalem (Israel), 4.–9. Juli 1999, II-375.)

Optical and Thermal Improvements of PV Performance by a Flowing Film of Water at the Frontside of PV Generators. - Krauter, Stefan; Schmid, U. (Proceedings of the 9th Sede Boquer Symposium on Solar Electricity Production, Sede Boquer (Israel), 12.–13. Juli 1999, S. 123–126)

Híbridos Termo/Solares Fotovoltaicos (Combined Solar–Thermal/Photovoltaic Systems) - Krauter, Stefan (Proceedings of Workshop Energias Alternativas para Produção de Calor, Frio e Geração e Conservação de Energia Elétrica, UFSC, Florianópolis, Santa Catarina (Brasilien), 6.–9. Dezember 1999)

Combined PV and Solar Thermal Systems for Facade Integration and Building Insulation - Krauter, Stefan; Araujo, G.; Schroer, S.; Salhi, M.; Triebel, C.; Hanitsch, Rolf (Solar Energy)

Basic Properties of Double Pullback Graph Transitions - Ehrig, Hartmut; Heckel, Reiko; Llabrés, Mercé; Orejas, Fernando

UML Collaboration Diagrams and Their Transformation to Java - Engels, Gregor; Hücking, Roland; Sauer, Stefan; Wagner, Annika

SOCCA Extended with UML like Packages - Engels, Gregor; Jan t'Hoen, Pieter; Dassen, Ray; Groenewegen, Luuk; G. Sprinkhuizen-Kuyper, Ida; Koopman, Pieter

A Formalisation of SOCCA using Z, part 1: The Type Level Concepts - Engels, Gregor; Dassen, Ray; Groenewegen, Luuk; G. Sprinkhuizen-Kuyper, Ida; Koopman, Pieter; Jan t'Hoen, Pieter
This document starts the formalisation of the modelling language of the SOCCA OO method in the formal specification language Z. It captures the `static' aspects of SOCCA, i.e. the meaning of SOCCA language elements at the type level, rather than `dynamic' aspects (dealing with the instance level (objects in execution)). It is restricted to core SOCCA; proposed extensions are not formalised.

UML-basierte Modellierung von Multimediaanwendungen - Sauer, Stefan; Engels, Gregor (Modellierung 1999, Workshop der Gesellschaft für Informatik e. V. (GI), März 1999 in Karlsruhe)
Der Entwicklungsprozeß von Multimediaanwendungen sollte ebenso wie der herkömmlicher Softwaresysteme eine Analyse und einen Entwurf beinhalten. In dieser Arbeit diskutieren wir, inwiefern die Modellierung der Struktur und des dynamischen Verhaltens einer Multimediaanwendung über die Modellierung herkömmlicher Software hinausgeht. Wir zeigen, daß Aspekte der Benutzungsschnittstelle und das Zeitverhalten integraler Bestandteil der Modellierung sein sollten. Als Ergebnis stellen wir die objektorientierte Modellierungssprache OMMMA-L vor, die auf der Unified Modeling Language (UML) aufbaut. Die Struktur- und Verhaltensdiagramme von UML wurden analysiert und gemäß der Charakteristika von Multimedia adaptiert bzw. erweitert. Im Klassendiagramm werden die Medientypen und die logische Struktur der Anwendung modelliert. Als Verhaltensdiagramme werden spezialisierte Sequenz- und Zustandsdiagramme eingesetzt. Mit dem Layoutdiagramm wird ein neuer Diagrammtyp hinzugefügt, der die integrierte und anschauliche Beschreibung der visuellen Darstellung und interaktiver Benutzereingaben einer Multimediaanwendung erlaubt. Neben der Vorstellung der einzelnen Diagrammtypen geben wir ein aus dem Metamodell zu UML abgeleitetes OMMMA-L-Metamodell an, in dem das Zusammenspiel der Modellelemente aus den verschiedenen Diagrammen spezifiziert wird.

OMMMA: An Object-Oriented Approach for Modeling Multimedia Information Systems - Sauer, Stefan; Engels, Gregor (Proceedings of the workshop on Multimedia Information Systems (MIS 1999), Indian Wells, CA (USA))
We present an object-oriented approach based on the Unified Modeling Language (UML) for modeling structure and dynamic behavior of a multimedia information system. We extend the Model-View-Controller paradigm for interactive systems towards multimedia and show that aspects of the graphical user interface and time-dynamic behavior ought to be integral parts of a model. This is done in the intention of achieving a coherent model of a multimedia information system. As a result, we present OMMMA-L a UML-based language for the Object-Oriented Modeling of MultiMedia Applications. OMMMA-L deploys class and state diagrams of UML as well as an extended sequence diagram and a newly introduced presentation diagram to adequately specify the visual presentation within a multimedia information system. In addition to explaining the different diagram types, we also define pragmatic rules on how to deploy and combine the various diagrams. Additionally, we relate OMMMA-L to basic ideas of multimedia information systems.

An Algebra of Graph Derivations using Finite (co-) limit Double Theories - Corradini, Andrea; Große-Rhode, Martin; Heckel, Reiko (Selected papers of the 13th International Workshop on Recent Trends in Algebraic Development Techniques (WADT 1998), Lisbon (Portugal))

From SOS Specifications to Structured Coalgebras: How to Make Bisimulation a Congruence - Corradini, Andrea; Heckel, Reiko; Montanari, Ugo (Proceedings of the 2nd workshop on Coalgebraic Methods in Computer Science (CMCS 99))

Dynamic Meta Modelling: A Graphical Approach to Operational Semantics - Engels, Gregor; Heckel, Reiko; Sauer, Stefan (Proceedings of the workshop on Rigorous Modeling and Analysis with the UML: Challenges and Limitations (satellite event of the Conference on Onject-Oriented Programming, Systems, Languages, and Applications (OOPSLA 1999)), Denver, CO (USA))
In this paper, dynamic meta modeling is proposed as a new approach to the operational semantics of behavioral UML diagrams. The dynamic meta model extends the well-known static meta model by a specification of the system’s dynamics by means of collaboration diagrams. In this way, it is possible to define the behavior of UML diagrams within UML. The conceptual idea is inherited from Plotkin’s structured operational semantics (SOS) paradigm, a style of semantics specification for concurrent programming languages and process calculi: Collaboration diagrams are used as deduction rules to specify a goal-oriented interpreter for the language. The approach is exemplified using a fragment of UML statechart and object diagrams. Formally, collaboration diagrams are interpreted as graph transformation rules. In this way, dynamic UML semantics can be both mathematically rigorous so as to enable formal specifications and proofs and, due to the use of UML notation, understandable without prior knowledge of heavy mathematic machinery. Thus, it can be used as a reference by tool developers, teachers, and advanced users.

MVC-Based Modeling Support for Embedded Real-Time Systems - Engels, Gregor; Sauer, Stefan (Proceedings of OMER Workshop, Herrsching, Germany)
Several software architecture paradigms have been proposed for the development of interactive software systems and applications. Their common idea is the separation of user interface components from application logic. Normally, they are deployed as design patterns or basic frameworks of interactive systems. Deploying these architecture paradigms for multimedia systems or embedded real-time systems, first requires an appropriate adaption to the specific aspects of these application areas. We will compare within this position paper two well-known architecture paradigms and motivate an advanced architecture paradigm applicable to real-time, embedded multimedia systems. In addition, we will discuss that the architecture paradigm should be reflected within the structure of a modeling language.

An Assessment of Aspect Language Design - Mehner, Katharina; Wagner, Annika (Proceedings of the Young Researchers Workshop (satellite event of the Generative and Component-Based Software Engineering (GCSE 1999)), Erfurt (Germany))

On the Role of Method Families in Aspect Oriented Programming - Mehner, Katharina; Wagner, Annika (Proceedings of the ECOOP Workshop on Aspect Oriented Programming, Lisboa (Spain))

Personalmanagement in Europa - Ein Vergleich auf der Basis empirischer Daten - Hanel, U; Kabst, Rüdiger; Mayrhofer, W; Weber, W

Die Bedeutung betrieblicher Informationskanäle: Eine Analyse vor dem Hintergrund aktueller personalwirtschaftlicher Entwicklungen - Kabst, Rüdiger; Weber, W (Mitbestimmung: Gesellschaftlicher Auftrag und ökonomische Ressource)

Kernel- and Locally Weighted Regression -- with Application to Time Series Decomposition - Feng, Yuanhua

Zunehmende Konfliktregulierung durch Arbeitsgerichte? Eine ökonomische Analyse der Häufigkeit von Kündigungsschutzprozessen - Frick, Bernd; Schneider, Martin

Kundenbindung aus Kundensicht: Konzeptualisierung, Optionalisierung, Verhaltenswirksamkeit - Eggert, Andreas

Implementation fächer- und lernortübergreifender Ausbildungskonzepte im Alltag dualer Ausbildung. Konzepte und Erfahrungen - Kremer, H.-Hugo (Lehren und Lernen in Schule und Betrieb)

Ein Vorgehensmodell für die Multimedia-Entwicklung mit Autorensystemen - Depke, Ralph; Engels, Gregor; Mehner, Katharina; Sauer, Stefan; Wagner, Annika (Informatik Forschung und Entwicklung)
Multimedia-Anwendungen sind interaktive Softwaresysteme und verlangen als solche, mit softwaretechnischen Methoden erstellt zu werden. Sie werden heutzutage in der Regel mit Hilfe von Autorensystemen entwickelt, die eine Ad-hoc-Entwicklung auf Implementierungsniveau unterstützen. Hierdurch und wegen des Fehlens etablierter Vorgehensmodelle für die Multimedia-Softwareentwicklung reduziert sich der Multimedia-Entwicklungsprozeß auf die Implementierungsphase. Dies führt zu den in der Softwaretechnik bekannten Problemen wie mangelnder Konzeption und fehlender Dokumentation. Wir stellen in diesem Beitrag ein Vorgehensmodell für die Entwicklung von Multimedia-Anwendungen vor, in dessen Mittelpunkt eine Analyse- und Entwurfsphase im Hinblick auf eine Implementierung der Multimedia-Anwendung mit einem Autorensystem stehen. Ausgehend von einem frameworkbasierten Analysemodell der Anwendung und einem Modell der Realisierungsmöglichkeiten mit einem konkreten Autorensystem wird systematisch ein Implementierungsmodell auf Instanzebene abgeleitet, das als Eingabe für das Autorensystem verwendet wird. Das postulierte Vorgehensmodell wird exemplarisch für das Autorensystem Director am Beispiel der Domäne multimedialer Lehr-/Lernanwendungen erläutert.

Formalization of the development process for a software-hardware reflexodiagnostic tool - Cherchago, Alexey; Finaev, V. (Scientific bulletin of Academy of Information Technologies in Education, Science and Balneology)

Graph Transformation for Specification and Programming - Andries, Marc; Engels, Gregor; Habel, Annegret; Hoffmann, Berthold; Kreowski, Hans-Jörg; Kuske, Sabine; Plump, Detlef; Schürr, Andy; Taentzer, Gabriele (Science of Computer Programming)
The framework of graph transformation combines the potentials and advantages of both, graphs and rules, to a single computational paradigm. In this paper we present some recent developments in applying graph transformations as a rule-based framework for the specification and development of systems, languages, and tools. After reviewing the basic features of graph transformation, we discuss a selection of applications, including the evaluation of functional expressions, the specification of an interactive graphical tool, an example specification of abstract data types, and the definition of a visual database query language. The case studies indicate the need for suitable structuring principles which are independent of a particular graph transformation approach. To this end, we present the concept of a transformation unit, which allows systematic and structured specifications and programming based on graph transformation.

Handbook of Graph Grammars and Computing by Graph Transformation: Vol. 2: Applications, Languages, and Tools - Ehrig, Hartmut; Engels, Gregor; Kreowski, Hans Jörg; Rozenberg, Grzegorz
Graph grammars originated in the late 60s, motivated by considerations about pattern recognition and compiler construction. Since then, the list of areas which have interacted with the development of graph grammars has grown quite impressively. Besides the aforementioned areas, it includes software specification and development, VLSI layout schemes, database design, modeling of concurrent systems, massively parallel computer architectures, logic programming, computer animation, developmental biology, music composition, visual languages, and many others. The area of graph grammars and graph transformations generalizes formal language theory based on strings and the theory of term rewriting based on trees. As a matter of fact, within the area of graph grammars, graph transformation is considered as a fundamental computation paradigm where computation includes specification, programming, and implementation. Over the last three decades, graph grammars have developed at a steady pace into a theoretically attractive and important-for-applications research field. Volume 2 of the indispensable Handbook of Graph Grammars and Computing by Graph Transformations considers applications to functional languages, visual and object-oriented languages, software engineering, mechanical engineering, chemical process engineering, and images. It also presents implemented specification languages and tools, and structuring and modularization concepts for specification languages. The contributions have been written in a tutorial/survey style by the top experts in the corresponding areas. This volume is accompanied by a CD-Rom containing implementations of specification environments based on graph transformation systems, and tools whose implementation is based on the use of graph transformation systems.

A View-based Approach to System Modeling Based on Open Graph Transformation Systems - Heckel, Reiko; Engels, Gregor; Ehrig, Hartmut; Taentzer, Gabriele (Handbook of Graph Grammars and Computing by Graph Transformations, Volume 2: Applications, Languages and Tools)
The idea of a combined reference model- and view-based specification approach has been proposed recently in the software engineering community. In this chapter we present a specification technique based on open graph transformation systems (in the double-pushout approach) by a new loose semantics for rule-based systems, which allows to model the interaction between different views, and by explicit frame conditions which restrict these interactions to an interface of open types. On this background, formal notions of view and view relation are developed and the behavior of views is described by the loose semantics. Based on the assumption that dependencies between different views are faithfully described by a common reference model, a construction is developed for the automatic integration of views. The views and the reference model are kept consistent manually, which is the task of a model manager. All concepts and results are illustrated at the well-known example of banking system.

Classification and Comparison of Module Concepts for Graph Transformation Systems - Heckel, Reiko; Engels, Gregor; Ehrig, Hartmut; Taentzer, Gabriele (Handbook of Graph Grammars and Computing by Graph Transformations, Volume 2: Applications, Languages and Tools)
In this chapter we use a three-level approach for analyzing module concepts for graph transformation systems. Based on the observation that module architectures consist of basic specications like body or export interface and relations like the implementation relation between them, or the import relation between a client and a server module, module concepts are characterized by answering the questions 1. What are the basic specifications? 2. Which relations between specifications are used? 3. How are specifications and relations combined to module architectures? These three questions are investigated for five module concepts available in the literature. As a reference example, a samplemodular specification of resource management in distributed operating systems is presented.

Kundenbindung aus Kundensicht: Konzeptualisierung, Operationalisierung, Verhaltenswirksamkeit

Depth profile of the implantation-enhanced intermixing of Ga+ focused ion beam in AlAs/GaAs quantum wells - Eshlaghi, Soheyla; Meier, Cedrik; Suter, Dieter; Reuter, D.; Wieck, A. D. (Journal of Applied Physics)

Realisierung fächer- und lernortübergreifender Ausbildungskonzepte - Kremer, H.-Hugo (Lehren und Lernen in der Aus- und Weiterbildung)

Lernfelder - Motor didaktischer Innovationen - Kremer, H.-Hugo; Sloane, Peter F. E. (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Can students act? Explorative Studie zum Erfolg fächer- und lernortübergreifender Maßnahmen - Kremer, H.-Hugo (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Das virtuelle Seminar "Wirtschaftspädagogik Köln-München" - Kremer, H.-Hugo; Wilbers, K. (Virtus, virtuelle Universitätssysteme Köln: Jahresbericht 1998/1999)

Der implizite Lerner in multimedialen Lernarrangements - Kremer, H.-Hugo; Sloane, Peter F. E. (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Towards Quality of Service for Parallel Computing: An Overview of the MILAN Project - Karl, Holger (High-Performance Computing and Networking, 7th International Conference, HPCN Europe 1999, Amsterdam, The Netherlands, April 12-14, 1999, Proceedings)

Coscheduling through Synchronized Scheduling Servers -- A Prototype and Experiments - Karl, Holger (Parallel and Distributed Processing, 11 IPPS/SPDP'99 Workshops Held in Conjunction with the 13th International Parallel Processing Symposium and 10th Symposium on Parallel and Distributed Processing, San Juan, Puerto Rico, USA, April 12-16, 1999, Proceedings)

Schwingungsanalyse von vorgespannten Schaufeln mit Deckplatten im Schaufelkranz - Popp, Karl; Sextro, Walter (Forschungsvereinigung Verbrennungskraftmaschinen (FW) -lnformationstagung Turbinen)

Experimental verification of a non-Hertzian contact model - Sextro, Walter (International conference on computational methods in contact mechanics)

Forced Vibration of Elastic Structures with Friction Contacts - Sextro, Walter (ASME Design Engineering Technical Conferences)

Ein ebenes Reibkontaktmodell zur Berechnung von Schaufelschwingungen mit Reibelementen - Sextro, Walter; Popp, Karl (Zeitschrift für angewandte Mathematik und Mechanik (ZAMM))

Schwingungsanalyse von vorgespannten Schaufeln mit Deckplatten im Schaufelkranz - Sextro, Walter; Popp, Karl (Forschungsvereinigung Verbrennungskraftmaschinen (FW))

Financial Participation in Europe: Determinants and Outcomes - Festing, M; Groening, Y; Kabst, Rüdiger (Economic and Industrial Democracy.)

Layout for a wind-power-driven, reverse osmosis installation for desalting brackish water in operation on an island - Bendfeld, Jörg; Bettenwort, Gerd; Ortjohann, Egon; Voss, Jürgen (Proceedings of the 1999 European Wind Energy Conference, 1-5 March 1999 Nice, France, pp975-978)

Hanif Kureishi. My Beautiful Laundrette

British Literature and Culture. Divergent Views and Attitudes. On the Occasion of Gerd Stratmann's 60th Birthday

Shortest-Path Routing in Arbitrary Networks - Meyer auf der Heide, Friedhelm; Vöcking, Berthold (Journal of Algorithms)

Allocating Weighted Jobs in Parallel - Berenbrink, P.; Meyer auf der Heide, Friedhelm; Schröder, K. (Theory of Computing Systems)

The computation of lyapunov exponents via spatial integration with application to blowout bifurcations - Aston, Philip J.; Dellnitz, Michael (Computer Methods in Applied Mechanics and Engineering)

On the Approximation of Complicated Dynamical Behavior - Dellnitz, Michael; Junge, Oliver (SIAM Journal on Numerical Analysis)

Computation of Essential Molecular Dynamics by Subdivision Techniques - Deuflhard, Peter; Dellnitz, Michael; Junge, Oliver; Schütte, Christof (Computational Molecular Dynamics: Challenges, Methods, Ideas)

Das neue europäische Schadenersatzrecht - Krimphove, Dieter (Österreichische Juristenzeitschrift (ÖJZ))

Ein Internet-Client für ein Geo-Informationssystem zur Visualisierung geowissenschaftlicher Daten - Lenz, C.; Stüwe, J.D.; Domik, Gitta; Gaulke, J.

Visualizing Complicated Dynamics - Bürkle, David; Dellnitz, Michael; Junge, Oliver; Rumpf, Martin; Spielberg, Michael (Proceedings of Visualization 99)

International Workshop on Communication and Data Management in Large Networks - Mayr, E. W.; Meyer auf der Heide, Friedhelm; Wanka, Rolf (Informatik aktuell)

Provably Good and Practical Strategies for Non-uniform Data Management in Networks - Meyer auf der Heide, Friedhelm; Vöcking, Berthold; Westermann, Matthias (Algorithms - ESA’ 99)

An Economic Analysis of the Law of Good-Faith Purchase in European Property Law - Krimphove, Dieter (Gdanskie Strudia Prawnicze)

The Philips/RWTH system for transcription of broadcast news - Beyerlein, Peter; Aubert, Xavier L.; Haeb-Umbach, Reinhold; Harris, Matthew J.; Klakow, Dietrich; Wendemuth, Andreas; Molau, Sirko; Pitz, Michael; Sixtus, Achim (Eurospeech)
This paper contains a description of the Philips/RWTH 1998 HUB4 system which has been build in a joint e ort of Philips Research Laboratories Aachen and Aachen University of Technology. We will focus our discussion on recent improvements compared to the original 1997 HUB4 system and evaluate them on the HUB4'97 evaluation data. The paper will deal with 1. a rough system overview including feature extraction, acoustic training, audio stream segmentation, and decoding 2. log-linear interpolation of distance-language models, 3. and the integration of various acoustic and language models via Discriminative Model Combination (DMC). The performance of the described system is 23% (relative) better than the performance of the 1997 Philips HUB4 system. A word error rate of 17.9% was achieved on the 1997 HUB4 evaluation set, compared to 23.5% using the original 1997 system.

The Philips/RWTH System for Transcription of Broadcast News - Beyerlein, Peter; Aubert, Xavier L.; Haeb-Umbach, Reinhold; Harris, Matthew J.; Klakow, Dietrich; Wendemuth, Andreas; Molau, Sirko; Pitz, Michael; Sixtus, Achim (Broadcast News Transcription and Understanding Workshop, Washington)
This paper contains a description of the Philips/RWTH 1998 HUB4 system which has been build in a joint e ort of Philips Research Laboratories Aachen and Aachen University of Technology. We will focus our discussion on recent improvements compared to the original 1997 HUB4 system and evaluate them on the HUB4'97 evaluation data. The paper will deal with 1. a rough system overview including feature extraction, acoustic training, audio stream segmentation, and decoding 2. log-linear interpolation of distance-language models, 3. and the integration of various acoustic and language models via Discriminative Model Combination (DMC). The performance of the described system is 23% (relative) better than the performance of the 1997 Philips HUB4 system. A word error rate of 17.9% was achieved on the 1997 HUB4 evaluation set, compared to 23.5% using the original 1997 system.

Investigations on inter-speaker variability in the feature space - Haeb-Umbach, Reinhold (ICASSP99 Phoenix, AZ)
We apply Fisher variate analysis to measure the effectiveness of speaker normalization techniques. A trace criterion, which measures the ratio of the variations due to different phonemes compared to variations due to different speakers, serves as a first assessment of a feature set without the need for recognition experiments. By using this measure and by recognition experiments we demonstrate that cepstral mean normalization also has a speaker normalization effect, in addition to the well-known channel normalization effect. Similarly vocal tract normalization (VTN) is shown to remove inter-speaker variability. For VTN we show that normalization on a per sentence basis performs better than normalization on a per speaker basis. Recognition results are given on Wall Street Journal and Hub-4 databases

An Investigation of Cepstral Parameterisations for Large Vocabulary Speech Recognition - Haeb-Umbach, Reinhold; Loog, Marco (Eurospeech)
We examined variants of MFCC and PLP cepstral parameterisations in the context of large vocabulary continuous speech recognition under different acous-tical environmental conditions: Compared to MFCC, mel-frequency PLP uses a cubic root intensity-to-loudness law, and an LPC analysis is applied to the mel-warped spectrum. In LPC-smoothed MFCC, the only difference to MFCC is the additional LPC smoothing of the warped spectrum. While neither technique was able to significantly outperform the MFCC parameterisation in our setup which includes an LDA feature transformation, feature set combination via DMC at the acoustic likelihood level and via ROVER at the recognized word level delivered small but consistent improvements.

A study of broadcast news audio stream segmentation and segment clustering - Harris, Matthew J.; Aubert, Xavier L.; Haeb-Umbach, Reinhold; Beyerlein, Peter (Eurospeech)
In transcription of broadcast news, dividing the signal into homogeneous segments, and clustering together similar segments is important. Decoding a complete broadcast news program in one chunk is technically di cult. Also, through creation of homogeneous clusters of segments, improvement from adaptation can be increased. Two systems of segmentation and clustering are compared. The best system used the BIC algorithm to produce long, homogeneous segments, and a nearest neighbour bottom-up agglomerative clustering algorithm to produce homogeneous clusters. Adaptation brought a word error rate (WER) improvement from 23:4% to 21:0% using the automatic segmentation and clustering, compared to an improvement from 21:8% to 20:0% using a handmade \correct" segmentation and clustering.

Kooperative Arbeitsplattformen - CSCW-Systeme in Lehr- und Lernkontexten - Schulte, Carsten; Selke, Harald; Huth, Carsten (LOG IN)

Dekonstruktion von Informatiksystemen als Unterrichtsmethode - Zugang zu objektorientierten Sichtweisen im Informatikunterricht - Hampel, Thorsten; Magenheim, Johannes; Schulte, Carsten (INFOS)

Fuzzy rules in case-based reasoning - Hüllermeier, Eyke; Dubois, D.; Prade, H. (In Proceedings RàPC-1999, Raisonnement à partir de Cas, Paris Palaiseau, France, In Conferences AFIA-1999)

Some New Aspects of Neoclassical Investment Theory with Taxes - König, Rolf; Sureth-Sloane, Caren

Toward a probabilistic formalization of case-based inference - Hüllermeier, Eyke (in Proceedings IJCAI-99, 16th international Joint Conference on Artificial Intelligence, Stockholm, Sweden)

Exploiting similarity for supporting data analysis and problem solving - Hüllermeier, Eyke (In Proceedings IDA-1999, 3th International Symposium on Intelligent Data Analysis, Amsterdam, Netherlands)

Extensions of a qualitative approach to case-based decision making: Unvertainty and fuzzy quantification in act evaluation - Hüllermeier, Eyke; Dubois, D.; Prade, H. (in Proceedings EUFIT-99 7th European Congress on Intelligent Techniques and Soft Computing, Aachen, Germany)

Toward models of case-based decision making - Hüllermeier, Eyke (in Proceedings EUFIT-99 7th European Congress on Intelligent Techniques and Soft Computing, Aachen, Germany)

A possibilistic formalization of case-based reasoning and decision making - Hüllermeier, Eyke (in Proceedings of the 6th International Conference on Computational Intelligence, Dortmund, Germany)

Aktuelle Rechtsfragen des Börsentermin- und Optionshandels -Anforderungen an Bank und Kunde- - Krimphove, Dieter

Numerical methods for fuzzy initial value problems - Hüllermeier, Eyke (International Journal of Uncertainty, Fuzziness and Knowledge-Based Systems)

Approximation of uncertain funtional relationships - Hüllermeier, Eyke (Fuzzy Sets and Systems)